Genotype-Dependent Efficacy of a Dual PI3K/mTOR Inhibitor, NVP-BEZ235, and an mTOR Inhibitor, RAD001, in Endometrial Carcinomas - Shoji, Keiko (Public Library of Science, 2012)
The PI3K (phosphatidylinositol-3-kinase)/mTOR (mammalian target of rapamycin) pathway is frequently activated in endometrial cancer through various PI3K/AKT-activating genetic alterations. We examined the antitumor effect of NVP-BEZ235—a dual PI3K/mTOR inhibitor—and RAD001—an mTOR inhibitor—in 13 endometrial cancer cell lines, all of which possess one or more alterations in PTEN, PIK3CA, and K-Ras. We also combined these compounds with a MAPK pathway inhibitor (PD98059 or UO126) in cell lines with K-Ras alterations (mutations or amplification). PTEN mutant cell lines without K-Ras alterations (n = 9) were more sensitive to both RAD001 and NVP-BEZ235 than were cell lines with K-Ras alterations (n = 4). Dose-dependent growth suppression was more drastically induced by NVP-BEZ235 than by RAD001 in the sensitive cell lines. G1 arrest was induced by NVP-BEZ235 in a dose-dependent manner. We observed in vivo antitumor activity of both RAD001 and NVP-BEZ235 in nude mice. The presence of a MEK inhibitor, PD98059 or UO126, sensitized the K-Ras mutant cells to NVP-BEZ235. Robust growth suppression by NVP-BEZ235 suggests that a dual PI3K/mTOR inhibitor is a promising therapeutic for endometrial carcinomas. Our data suggest that mutational statuses of PTEN and K-Ras might be useful predictors of sensitivity to NVP-BEZ235 in certain endometrial carcinomas.